Addressing usability quality attributes in techo-spritual application - Abdul Wahab, Ahairul Afza; Kamaruddin, Azrina; Hassan, Sa'adah; Che Pa, Noraini (School of Computing, UUM College of Arts and Sciences, 2017)
Usability studies are conducted extensively for web sites and other applications. One of the domains that need attention is techno-spritual application. To date, the demand for techno-spritual application is increasing. This suggests that the application design must inhibit usability and also positive user experience. Thus, this study is conducted to explore its’ usage usability. The Post-Study System Usability Questionnaire (PSSUQ) has been used to gather the user’s feedback focusing on the mobile Holy Quran, one of the techno- spiritual type application for Muslims. The results show that improving the usability attributes of techno-spiritual mobile application can have a positive influence for the mobile application usability and adoption. The study will be beneficial for the application provider in the field of techno-spiritual software development industry.